Difficulties in diagnosing paroxysmal nocturnal hemoglobinuria in a municipal internal disease hospital - Aigul R. Zinnatullina; Gennady P. Ishmurzin (Клиническая практика, 2022)
Background: The purpose of this work is to present a case of paroxysmal nocturnal hemoglobinuria in the clinical practice of an internist for the purpose of differential diagnosis with other diseases with the jaundice syndrome in a city hospital.